2015
DOI: 10.4103/2231-0762.161764
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and behavioral determinants of tobacco use among 13-15 year old school children

Abstract: Background:The epidemic of tobacco use is one of the greatest threats to global health today. Tobacco attributable deaths in India currently range from 800,000 to 900,000 per year. Adolescents are among the most vulnerable group to start tobacco use. Information on tobacco use among the youth is necessary to establish control measures against it.Objectives:To assess the knowledge, attitude, and behavioral determinants of tobacco use among high school students (age13–15 years) in Bangalore.Materials and Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…A study by Raina has found out that about 46.4% of the study subjects thought that smoking does not help in gaining or losing weight. 16 In the present study father was a smoker in 35.7% cases, and TV was best source of information on smoking as viewed by 58.7%. In rural 91.23% see actors smoking in movies and 99.42% in urban areas see actors smoking in movies.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…A study by Raina has found out that about 46.4% of the study subjects thought that smoking does not help in gaining or losing weight. 16 In the present study father was a smoker in 35.7% cases, and TV was best source of information on smoking as viewed by 58.7%. In rural 91.23% see actors smoking in movies and 99.42% in urban areas see actors smoking in movies.…”
Section: Discussionmentioning
confidence: 46%
“…15 Majority of the study population [94.4% (472/500)] believed that smoking is definitely harmful to health. 16 Knowledge of and attitude regarding the bad effects of smoking was generally satisfactory in both groups regarding, its consequences on health. 15 Smoking has many adverse effects especially in terms of non-communicable diseases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Memon et al 23 found that 47% of smokers wanted to stop smoking. Raina et al 24 revealed in a study that 53.3% cigarette users expressed the desire to stop smoking. All these studies indicate that there is a positive attitude towards quitting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen in other studies in India. 15 However the same in GYTS Delhi was less than 26%. 6 Few other studies also reported low levels of knowledge in their study population.…”
mentioning
confidence: 99%